2023
DOI: 10.1088/1361-6498/accaf1
|View full text |Cite
|
Sign up to set email alerts
|

Eye lens dose for medical staff assisting patients during computed tomography: comparison of several types of radioprotective glasses

Abstract: Medical staff sometimes assists patients in the examination room during computed tomography (CT) scans for several purposes. This study aimed to investigate the dose reduction effects of four radioprotective glasses with different lead equivalents and shield shapes. A medical staff phantom was positioned assuming body movement restraint of the patient during chest CT, and air kerma at the eye surfaces of the medical staff phantom and inside the lens of the four types of radioprotective glasses were measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Conversely, Endo et al reported that 0.75 mmPb protective glasses are heavy and cause discomfort to the surgeon, although the glasses demonstrated an excellent shielding effect [24]. The use of protective glasses with a higher lead equivalent is recommended in CT examinations because of the short wearing time [25]. Additionally, the use of CT-specific protective plates and protective curtains may further reduce exposure to the lenses of assistants [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Endo et al reported that 0.75 mmPb protective glasses are heavy and cause discomfort to the surgeon, although the glasses demonstrated an excellent shielding effect [24]. The use of protective glasses with a higher lead equivalent is recommended in CT examinations because of the short wearing time [25]. Additionally, the use of CT-specific protective plates and protective curtains may further reduce exposure to the lenses of assistants [26,27].…”
Section: Discussionmentioning
confidence: 99%